Early Onset of Tenofovir-Induced Renal Failure: Case Report and Review of the Literature - Shilpa M. Patel; Teresa R. Zembower; Frank Palella; Yashpal S. Kanwar; Shubhada N. Ahya (The Scientific World Journal)
Tenofovir is an acyclic nucleotide analogue reverse transcriptase inhibitor that is commonly prescribed as part of a highly active antiretroviral therapy (HAART) regimen in HIV-infected patients. Although it is generally well tolerated, renal insufficiency has been associated with its use. We report a biopsy-proven case of acute renal failure that developed within weeks of initiating a HAART regimen containing tenofovir, and review the literature with specific attention to cases of renal failure occurring within 8 weeks of tenofovir initiation. Our patient developed renal insufficiency within 3 weeks of initiating tenofovir-containing HAART and overt renal failure was noted within 5 weeks. Renal biopsy demonstrated histopathologic changes suggestive of HIV nephropathy, despite normal baseline serum creatinine values. Thirty additional cases of tenofovir-associated renal failure have been reported. In the majority (n = 22, 73%), renal failure occurred months after initiating therapy (range: 5–26 months). However, in a significant subset (n = 8, 27%), renal failure occurred within 8 weeks of treatment initiation. Our data suggest that some patients are at risk for developing renal failure within weeks of tenofovir initiation. Thorough evaluation of renal function should be undertaken before prescription of tenofovir-containing HAART. For those in whom subclinical renal disease is discerned, added vigilance when monitoring renal function may be warranted.